Den lille og den store nytte: Et interkulturelt perspektiv på forholdet mellem nytte og frihed - Garsdal, Jesper; Paulsen, Michael (Academic Quarter | Akademisk kvarter, 2016)
In this article, we expound a distinction between a “small” and a “large” notion of utility. We do this by linking the concept of utility to the concept of freedom. Our suggestions derive from two readings related to the Chinese history of philosophy. First, we develop the distinction in a reading of early classical Chinese philosophy, through a discussion of Confucianism, Mohism and Daoism. Secondly, we explore the relationship between utility and freedom in the meeting between Chinese thinking and modern western philosophy. We discuss Yan Fu’s translations of Western philosophy, particularly Mill. Through this discussion, we end up with situating the discussion of utility in the domain of human freedom. Finally, drawing on Schiller, we consider how utility and freedom should be cultivated giving rise to a kind of balance between “harmony” and “conflict” in contemporary global society.